Epidemiology of cervical cancer with special focus on India - Sreedevi A; Javed R; Dinesh A (Dove Medical Press, 2015)
Aswathy Sreedevi, Reshma Javed, Avani Dinesh Community Medicine, AIMS, Kochi, Amrita Vishwa Vidyapeetham, Kerala, India Abstract: Cervical cancer is on the declining trend in India according to the population-based registries; yet it continues to be a major public health problem for women in India. Multifactorial causation, potential for prevention, and the sheer threat it poses make cervical cancer an important disease for in-depth studies, as has been attempted by this paper. This paper attempts to review the available knowledge regarding the epidemiology and pattern of cervical cancer; types of HPV (human papilloma virus) prevalent among cervical cancer patients and among women in general, high-risk groups such as commercial sex workers, and HIV (human immunodeficiency virus)-positive women; and the role of the national program on cancer in control efforts. The peak age of incidence of cervical cancer is 55–59 years, and a considerable proportion of women report in the late stages of disease. Specific types of oncogenic HPV-16, 18 have been identified in patients with cervical cancer. Other epidemiological risk factors are early age at marriage, multiple sexual partners, multiple pregnancies, poor genital hygiene, malnutrition, use of oral contraceptives, and lack of awareness. A multipronged approach is necessary which can target areas of high prevalence identified by registries with a combination of behavior change communication exercises and routine early screening with VIA. Sensitizing the people of the area, including menfolk, is necessary to increase uptake levels. Vaccination against types 16 and 18 can also be undertaken after taking into confidence all stakeholders, including the parents of adolescent girls. Preventing and treating cervical cancer and reducing the burden are possible by targeting resources to the areas with high prevalence. Keywords: cervical cancer, HPV, screening, prevention, epidemiology, India